Surface-oriented heterostructure of iron metal organic framework confined molybdenum disulfides as an efficient bifunctional electrocatalyst for overall water splitting - Velayutham, R.; Raj, C. J.; Jang, H. M.; Cho, W. -J.; Palanisamy, K.; Kaya, C.; Kim, B. C. (ELSEVIER, 2023)
The rational design of binder free, non-noble, highly active, cost effective and durability of bifunctional elec-trocatalyst for efficient overall water splitting is crucial for acquiring clean hydrogen energy systems. Herein, a surface-oriented in-situ growth of molybdenum disulfide on the non-precious iron metal organic frameworks is implemented by straightforward two-step solvothermal method. The optimum Fe-MOF@MoS2-6h electrocatalyst heterostructures achieves the highly active heterointerfaces of MoS2 and Fe-MOF, facilitates the mass/charge transport of the catalyst which improves the electrical conductivity. As a consequence, the optimal Fe-MOF@-MoS2-6h achieves the lowest overpotential of-118 mV and-187 mV at 10 mA cm-2 for HER and OER, respectively, outperforming benchmark of Pt-C/NF and IrO2/NF. Moreover, an overall water splitting electro-lyzer constructed using Fe-MOF@MoS2-6h||Fe-MOF@MoS2-6h electrocatalyst, requires only a cell voltage of 1.517 V to achieve a current density of 10 mA cm-2 which is comparable to Pt-C/NF||IrO2/NF (1.588 V) water splitting device. The precisely rational designed bifunctional Fe-MOF@MoS2-6h electrode also revealed no degradation in the stability test at 50 mA cm-2 for 100 h in alkaline electrolyte. This work proposes a practical strategy for highly efficient heterointerface electrocatalysts to achieve promising electrochemical water splitting.
Keywords: Iron metal organic framework; Molybdenum disulfide; Surface-oriented; Bifunctional electrocatalyst; Overall water splitting; ONE-POT SYNTHESIS; HYDROGEN EVOLUTION; HIGHLY EFFICIENT; OXYGEN EVOLUTION; ALKALINE; NI3S2; NI; Science & Technology - Other Topics; Materials Science